Index investment strategy - Han, E-Lin (2008)
This study aims to formulate a portfolio model that replicates the returns of the Standard and Poor's 500 Index by minimising tracking error. Stock selection is based on stratified sampling and correlation between the stock and the index's returns. Effects of short selling constraint, rebalancing, and transaction costs are investigated.